The FOREIGN WORKER MANAGEMENT IN INDONESIA: POLICIES, PRACTICES AND OPTIMIZATION PATHS: POLICIES, PRACTICES AND OPTIMIZATION PATHS - Zhu, Xi (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2025)
This study systematically analyzes Indonesia's foreign labor management system and traces its policy evolution from strict control in the colonial period to contemporary multi-policy coordination. After twists and turns, it has now established a multi-link fine system based on the Labor Law, including labor access, work permits, residence visas, and rights protection. The responsibilities of multiple subjects are clear. The Immigration Bureau strictly guards the country's borders and controls visas and residences. The Ministry of Manpower regulates employment and mediates disputes. The Foreigners Supervision Group conducts regular inspections. Enterprises bear the main responsibility for employment management and strictly abide by laws and regulations from recruitment to welfare. Trade unions and non-governmental organizations are auxiliaries, providing services to promote integration and protecting labor rights in multiple dimensions. However, the existing problems are thorny. Policy implementation encounters cumbersome approval and weak supervision. Illegal labor is repeatedly banned. Labor rights are frequently violated through wage deductions and harsh working conditions. Differences hinder cultural integration in language and customs. Learn from Singapore's precise planning and fine control, as well as Malaysia's experience in industrial coordination, to optimize Indonesia's foreign labor management measures.